Penetapan Aspek Hukum Pidana Materiil Dalam Undang-Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual - SH.,MH., Sujasmin (PT. Data Jaringan Visual Indonesia (Djava), 2025)
ABSTRACT Sexual violence is a problem that actually occurs in people's lives, and is a form of attack and threat to the body, sexuality, and rights of women, children and in general related to the inequality of power relations between men and women. This sexual violence includes rape, molestation, sexual harassment, incest, and sexual exploitation in the formulation of criminal acts has been regulated in Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS). This study analyzes the determination of material criminal law aspects in the TPKS Law, it is known that there are several criminalizations of TPKS (Articles 4 to 14 of the TPKS Law), TPKS perpetrators (every person or corporation) are also strictly regulated by TPKS perpetrators in the formulation of their articles, targets / scope of TPKS victims (Article 15 of the TPKS Law), criminal sanctions for TPKS perpetrators in addition to being subject to imprisonment, and fines, as well as additional penalties in the form of restitution sanctions for TPKS victims (Article 16, Articles 30-38 of the TPKS Law), and sanctions in the form of medical rehabilitation and social rehabilitation for TPKS perpetrators (Article 17 of the TPKS Law). Keywords: Perpetrators, TPKS, and Victims.